2005
DOI: 10.1111/j.1460-9592.2005.01488.x
|View full text |Cite
|
Sign up to set email alerts
|

A noninvasive estimation of mixed venous oxygen saturation using near‐infrared spectroscopy by cerebral oximetry in pediatric cardiac surgery patients

Abstract: Regional cerebral oximetry via NIRS correlates with SvO2 obtained via invasive monitoring. However, the wide limits of agreement suggest that it may not be possible to predict absolute values of SvO2 for any given patient based solely on the noninvasive measurement of rSO2. Near-infrared spectroscopy, using the INVOS 5100 cerebral oximeter, could potentially be used to indicate trends in SVO2, but more studies needs to be performed under varying clinical conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
86
2
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(101 citation statements)
references
References 30 publications
8
86
2
5
Order By: Relevance
“…This would be especially useful for patients for whom invasive procedures are not suitable or who wish to avoid them. A correlation between the StO 2 and ScvO 2 has been show in similar studies such as that of Tortoriello et al, (2005), which used the NIRS system to evaluate the StO 2 in pediatric cardiac surgery. Another study used the NIRS system combined with transesophageal echocardiography to monitor the oxygen saturation of the left and right ventricles (Margreiter et al, 2002) and showed that NIRS was fully feasible for the evaluation of the oxygen saturation of internal organs and large blood vessels.…”
Section: Discussionsupporting
confidence: 54%
“…This would be especially useful for patients for whom invasive procedures are not suitable or who wish to avoid them. A correlation between the StO 2 and ScvO 2 has been show in similar studies such as that of Tortoriello et al, (2005), which used the NIRS system to evaluate the StO 2 in pediatric cardiac surgery. Another study used the NIRS system combined with transesophageal echocardiography to monitor the oxygen saturation of the left and right ventricles (Margreiter et al, 2002) and showed that NIRS was fully feasible for the evaluation of the oxygen saturation of internal organs and large blood vessels.…”
Section: Discussionsupporting
confidence: 54%
“…The main clinical applications are in neonatology [8,9], in which case the head can be transilluminated, and in coronary or carotid artery surgery [10][11][12][13][14][15][16][17][18]. Few studies have been published on use of NIRS in TBI [19,20], and the technique has not yet been convincingly validated for the indication TBI by comparison with other measures of cerebral oxygenation.…”
mentioning
confidence: 99%
“…The relative ischemia resulting from global cerebral vasoconstriction seems to be the main mechanism in pediatric patients, particularly neonates [11.13-15]. In contrast, the increase of SjO 2 (> 75%) when reaching the hypothermia temperature routinely observed [12,15,16], was not confirmed in all patients. Maybe it is due to the practice of establishing a flow based on age, temperature and mean arterial pressure, and then correct it by SvO2.…”
Section: Discussionmentioning
confidence: 99%